Analysis of Islamic Religious Education teachers' strategies in handling self-harm cases - Aulia, Fitri; Maesak, Cantri; Nurfadilla, Hikma; Harahap, Yasmin (Jurnal Iman dan Spiritualitas, 2025)
This study aims to examine in more depth how Islamic Religious Education teachers' strategies are in handling self-harm cases in elementary schools, especially in Elementary School (SDN) Cikampek Utara 3, and how effective the spiritual and educational approach is in overcoming the problem. Not only analyzing the strategies of Islamic Religious Education teachers carried out in overcoming self-harm cases against 6th-grade children at Elementary School Cikampek Utara 3, but also revealing the factors that cause a child to commit self-harm. This study employs a qualitative approach, specifically a case study. The case study used in this study is an Intrinsic Case Study. The case study aims to fulfil the researcher's personal interests in a particular problem. The data collected are in the form of words, stories, or analysis results, through conducting closed interviews. Other data collected also cites literature studies from relevant journals, books, and related websites. Islamic Religious Education (PAI) teachers have an important role in handling self-harm cases against grade 6 students. The strategies implemented by PAI teachers include emotional approaches, spiritual guidance, and providing education about religious values and the importance of self-care. PAI teachers also foster open communication with students and collaborate with parents and schools to create a safe and supportive environment. This study can be both theoretically and practically useful. Theoretical benefits are useful for readers or other research experts. For practical benefits, it is useful for campuses and academics at a higher education institution. And useful for students as a reference for new research. The novelty of this study lies in the research conducted at SDN Cikampek Utara 3, a school in the Karawang district. The benefits of this study are prioritized for employees or educators at SDN Cikampek Utara 3.